Analisis PDRB sektor primer dan kesempatan kerja di Kabupaten Bungo - Anis Mayanti; Syaparudin Syaparuddin; Erni Ahmad (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2013)
This study aims to see the development of value-added primary sector and sub sectors of primary, value-added contribution of primary sector and sub sectors of GDP primary Bungo district, the elasticity of value added of primary sector and sub sector of primary employment in primary sectors and sub sectors and primary factors - factors that influence the development of value-added primary sector over the period 2001-2010. In this study researchers used secondary data in the form of time series (time series) from 2001 to 2010. Data analysis used a model that is descriptive and quantitative analysis and simple regression using ordinary least squares regression. The analysis perkembagan primary sector value added growth tends to fluctuate and the average is pretty good as well as occurring in the development of primary sub-sector.The contribution of primary sector value added and primary sub sector to GDP is quite large Bungo Regency. From the analysis of the elasticity of value added of primary sector employment relations are elastic, the elasticity of value added sub sector of primary employment sub-sectors that have a primary elastic relationships contained in the sub-sector value-added food crops, plantation crops, livestock and their products, fisheries sub-sector of forestry,mining and quarrying in the elastic. The results of estimation of the factors that influence the development of value-added primary sector Bungo district when viewed together (in unison) that direct government spending variables and labor can provide a positive influence on GDP growth in the primary sector Bungo Regency. Tests showed that the partial direct government spending variables have a significant effect on GDP growth in the primary sector, while labor variables had no significant effect of primary sector GDP growth during the study period 2001-2010. Keywords:Gross Domestic Product, Agricultural, Primary Sector